How multilingual can a dubbed film be? Language combinations and national traditions as determining factors - Voellmer, Elena; Zabalbeascoa, Patrick (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
This paper analyses the German and Spanish dubbed versionsof Inglourious Basterds (Bender & Tarantino, 2009), two different translations of the same source text. In dialogue with relevant theory, we discuss the question of the extent to which a translated text can be heterolingual and how certain dubbing practices may prevent translations from being as heterolingual as their source texts. Our case study has also enabled us to find possible evidence of norms with regard to the translation of heterolingual films in Spain and in Germany. Linguistic variation is an important feature of Inglourious Basterds and it is both interlingual (different languages) and intralingual (dialects, sociolects and idiolects). Each dubbed version has its own initial situation and it is particularly interesting to see how linguistic variation is dealt with in translation. We propose the concept of ‘represented nationalities’ (similar to Delabastita’s 2010 “supposedly spoken” or “represented” languages) in the Spanish dubbed version of the film. As a theoretical contribution, we suggest that ‘intertextual translation’ is a more accurate term for translations of heterolingual texts (including dubbed versions) than Jakobson’s (1959) “interlingual translation”.